Digital Beamforming Features in Subaperture Antenna Arrays of Highly Informative Space Radars with Aperture Synthesis - S. V. Kozlov; V. V. Radionovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
It is shown that during digital beamforming in a subaperture antenna array of highly informative space radars with synthetic aperture, it is necessary to provide a procedure for equalizing the time delays of the subaperture output signals for transmission and reception. It has been established that losses in the signal-to-noise ratio on a radar image of a point target for a typical aperture size at an elevation angle of 0.7 m and a signal spectrum width of 600 MHz reach 2.1 and 7.5 dB for off-nadir angles of 21° and 50°, respectively. Recommendations are formulated for equalizing time delays for transmission and reception based on spectral processing. Simulation results are presented.